PENGEMBANGAN MATERI AJAR BAHASA INDONESIA DENGAN PENDEKATAN ETNOPEDAGOGI DI SD NEGERI 10 PEMECUTAN KELOD - Dewa Gede Bambang Erawan,; I Nyoman Suprsa,; I Gusti Agung Made Agung Dwipayana,; Ni Komang Triulan Cahyani,; Ni Made Mellia Putri Pradnyandari, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Success in implementing the learning process is completely under the control of the teacher. Therefore, teachers must have the ability to design learning tools. Based on the results of observations carried out at SD Negeri 10 Pemecutan Kelod, one of the problems found was that teachers experienced difficulties in preparing and developing teaching materials. Responding to this problem, the PkM implementing team intends to provide alternative solutions in the form of training and assistance in preparing Indonesian language teaching materials based on ethnopedagogy. The methods used to overcome these problems are lecture, discussion and simulation methods which are carried out in the form of training and mentoring. This method is expected to be able to improve teachers' understanding and skills in developing ethnopedagogy-based teaching materials. The output of this service includes PKM reports, national scientific journal articles, IPR video reports, PKM activity posters, mass media publications.